Pengaruh Penerapan Model Pembelajaran Problem Based Learning terhadap Hasil Belajar PPKN pada Siswa Kelas VII SMP Negeri 3 Sitiotio - Agnes Chintya Siringoringo; Hapni Laila Siregar (Pusat Riset dan Inovasi Nasional, 2025)
This study was conducted because the learning outcomes of students in PPKn lessons are still low. Based on observations, one of the main causes of low learning outcomes is the monotonous learning model and focuses on lectures, so that students are less motivated and not actively involved in the learning process. This study aims to determine the effect of implementing the problem-based learning (PBL) learning model on PPKn learning outcomes in grade VII students of SMP Nelgelri 3 Sitiotio. The research method used is a pretest-posttest control group design. This study uses a quantitative questionnaire research model, which involves data collection through observation, interviews, and documentation. The population of this study was all students of SMP Nelgelri 3 Sitiotio, and the sample of this study was grade VII students of Classes A and B. This study is a type of Quasi-Evaluative Test Type Non-Equivalent Control Group Test, which uses an interview group and a control group. Data were collected through observation, questionnaires, documentation, and test results sheets. The instrument used was the test results sheet. Data analysis techniques involve statistical calculations in the form of numerical data and comparing the average value of the posttest results between the experimental group and the control group. This research will be conducted on grade VII students of SMP Nelgri 3 Sitiotio, Delsa Holbung, Sitiotio District, Samosir Regency. The results of the study showed that the problem-based learning model had a significant effect on improving students' PPKn learning outcomes. The experiment group experienced an average increase of 24.19 points (from 47.62 to 71.81), while the control group only experienced an increase of 2.32 points (from 53.26 to 55.58). The results of the Paired Sample t-test showed a significance value of 0.000 <0.05, proving a significant difference between the pretest and posttest in the experiment group. The results of the Independent Samples t-Test test also showed a significance value of 0.000 <0.05, which means that the PBL model is more effective than conventional learning. The highest increase occurred in the ability to evaluate (C5) by 45%, followed by the ability to apply (C3) and analyze (C4) which each reached 96%. This study proves that the problem-based learning model can improve student learning outcomes in cognitive aspects in PPKn lessons and can be used as an alternative effective learning model.